2017
DOI: 10.5941/myco.2017.45.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Development and Molecular Characterization of Novel Polymorphic Genomic DNA SSR Markers inLentinula edodes

Abstract: Sixteen genomic DNA simple sequence repeat (SSR) markers of Lentinula edodes were developed from 205 SSR motifs present in 46.1-Mb long L. edodes genome sequences. The number of alleles ranged from 3–14 and the major allele frequency was distributed from 0.17–0.96. The values of observed and expected heterozygosity ranged from 0.00–0.76 and 0.07–0.90, respectively. The polymorphic information content value ranged from 0.07–0.89. A dendrogram, based on 16 SSR markers clustered by the paired hierarchical cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…The N A , H E , H O , and PIC values obtained from the study by Lee et al [23] were 4.9, 0.55, 0.31, and 0.51, respectively. Moon et al [24] reported the values of 6.8, 0.64, 0.32, and 0.61 for N A , H E , H O , and PIC, Figure 2. Clustering of distance-and model-based for 100 Lentinula edodes strains including 77 wild strains and 23 cultivars using 20 genomic SSR markers.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The N A , H E , H O , and PIC values obtained from the study by Lee et al [23] were 4.9, 0.55, 0.31, and 0.51, respectively. Moon et al [24] reported the values of 6.8, 0.64, 0.32, and 0.61 for N A , H E , H O , and PIC, Figure 2. Clustering of distance-and model-based for 100 Lentinula edodes strains including 77 wild strains and 23 cultivars using 20 genomic SSR markers.…”
Section: Discussionmentioning
confidence: 95%
“…The 20 SSR markers used in this study were selected in our two previous studies [23,24]. The features of selected markers in higher genetic diversity values such as polymorphic information content (PIC), expected and observed heterozygous, genotypes and allele numbers are presented in Table 1.…”
Section: Dna Extraction and Ssr Analysismentioning
confidence: 99%
“…This set of eight markers could differentiate among 20 L. edodes cultivars, with PIC values ranging from 0.269 to 0.764, with an average of 0.409 ( Table 2). Novel SSR markers for L. edodes were previously described by Lee et al [7] and Moon et al [8]. Lee et al [7] reported that the PIC values of 44 SSR markers with dinucleotide to pentanucleotide repeats ranged from 0.10 to 0.89, with an average of 0.511 and Moon et al [8] determined that the PIC values of 16 SSR markers with dinucleotide and trinucleotide repeats were between 0.07 and 0.89, with an average of 0.612.…”
Section: Discussionmentioning
confidence: 99%
“…Novel SSR markers for L. edodes were previously described by Lee et al [7] and Moon et al [8]. Lee et al [7] reported that the PIC values of 44 SSR markers with dinucleotide to pentanucleotide repeats ranged from 0.10 to 0.89, with an average of 0.511 and Moon et al [8] determined that the PIC values of 16 SSR markers with dinucleotide and trinucleotide repeats were between 0.07 and 0.89, with an average of 0.612. Our markers with tetranucleotide to hexanucleotide repeats were less useful for identifying individuals compared with the markers mainly comprising dinucleotide repeats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation